Spreaders. The professional choice (Эндодонтия Today, 2020)
The article considers the technical aspects of the use of different spreaders during root canal obturation by the cold lateral condensation technique. It was identified the influence of spreader penetration depth on the quality of apical and coronal obturation depending on a material and a diameter of a tool. The differentiated approach to the choice of a spreader was suggested for a high-quality obturation of curved canals by the cold lateral condensation technique.